Konsepsi Peran Guru Sebagai Fasilitator dan Motivator Dalam Proses Pembelajaran Pendidikan Agama Islam - Ali Mustofa Arif Muadzin (Jurnal Pendidikan Islam, 2021)
Facilities and motivation in learning are very important. This study discusses the role of the teacher as a facilitator and motivator in the learning process of Islamic religious education. The purpose of this study was to determine the role of the teacher as a facilitator and motivator, and the inhibiting factors in its implementation. To get answers to the problems above, the authors conducted qualitative research. After analyzing the data obtained, the results showed the readiness of the teacher, namely: The teacher provides all learning tools before learning begins (such as syllabus, curriculum, lesson plans, evaluation materials and teaching materials). ), Teachers provide learning facilities in the form of methods, media, and learning equipment, Teachers as partners not superiors and teachers do not act arbitrarily to students, and teachers are able to understand students well and provide learning experiences that are appropriate for students and intrinsically motivating. All of this can be achieved through a good understanding of a teacher regarding teacher theory as a facilitator and motivator. All aspects of education, the family and community environment should be in line with and support the teacher's role as a facilitator and motivator so that it can be realized properly.